Swallowing endoscopy findings in Huntington's disease: A case report - Alves, Thaís Coelho [UNESP]; Cola, Paula Cristina [UNESP]; dos Santos, Rarissa Rúbia Dallaqua [UNESP]; Motonaga, Suely Mayumi [UNESP]; da Silva, Roberta Gonçalves [UNESP] (FapUNIFESP (SciELO), 2016)
Huntington's disease (HD) is a degenerative genetic disorder with autosomal-dominant transmission. The triad of symptoms of this disease consists of psychiatric disorders, jerky movements, and dementia. Oropharyngeal dysphagia, which is more evident with disease progression, is also present. Few studies have addressed the swallowing characteristics using objective analysis in this population. The purpose of this research was to describe the swallowing endoscopic findings of the pharyngeal phase in HD. This is a cross-sectional study addressing a clinical case which included two individuals of the same family, male, 32 and 63 years old, designated as individual A and individual B, with progression of the disease for five and 13 years, respectively. Consistent liquid, nectar, and puree were offered during the evaluation. There was presence of posterior oral spillage in liquid and nectar, small amount of pharyngeal residues, and no laryngeal penetration or aspiration in the individuals with HD in this study.
Keywords: Chorea; Deglutition Disorders; Endoscopy; Huntington's Disease; Neurodegenerative Diseases